PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TYPE JIGSAW TERHADAP KETERAMPILAN PUKULAN UNDERHAND PERMAINAN BULUTANGKIS SISWA SMPN 4 SATAP KIRAK KABUPATEN MAMASA - Segion Segion; Suhardianto Suhardianto; Eka Fitriana HS; Aminuddin Aminuddin (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2026)
This research is motivated by the badminton game learning process conducted at SMPN 4 Satap Kirak, Mamasa Regency, badminton is a type of sport played one on one or two on two, players hit the ball with a racket. In badminton players must understand and master the basic techniques for hitting the ball (cock), known as forehand and backhand strokes. This study uses a quantitative approach, which is used is a pre-experiment with a one group pretest-posttest design, with a population of 20 students with a sampling technique carried out using the total sampling method so that the number of samples is equal to the number of populations, and data collection uses observation, tests and documentation. The results of the study showed that the average pretest value was 68.32, with an average posttest value of 80.41. The results of learning underhand strokes showed that the t count of 8,542 was greater than the t table of 2,093, and the two-tailed sig value was .001 less than 0.05. It can be concluded that the hypothesis is accepted, and there is a significant effect of the implementation of the cooperative learning (jigsaw) model on the underhand badminton skills of eighth-grade students at SMPN 4 Satap Kirak, Mamasa Regency.